Stability studies in oncology: A marketing tool for pharmaceutical companies, a scientific mission for hospital pharmacists. Issue 2 (April 2019) - Vigneron, Jean; D'Huart, Elise; Demoré, Béatrice
Abstract: Introduction: Hospital pharmacists, physicians, and nurses need stability information on the drugs used in their daily practice. The objectives of this work were to evaluate if the information given by pharmaceutical companies about the stability of reconstituted and diluted solutions in the field of oncology were sufficient in the daily practice of hospitals. Methods: The first step was to establish a list of the main needs about stability data on the basis of the daily practice of hospital pharmacists. The second step was to search through information given by pharmaceutical companies and then to compare to hospital pharmacists' needs. The third step was to find information in the cases, in which pharmaceutical companies' information was not sufficient. Results: The situation is different depending on the product. For originators, stability data given by pharmaceutical companies are often very limited, the goal being to obtain the marketing authorization. For generics or biosimilars, extended stability studies are carried out to conquer the market and are part of the marketing strategy. A list of studies to fill the gap of companies' information was presented. Examples including bortezomib, rituximab, azacitidine, nivolumab, and some mixtures were presented. The importance of stability studies conducted in hospitals is emphasized. Conclusion: Pharmaceutical companies perform stability studies for their products and for their own interest. In many cases, the results of these studies are insufficient and do not meet the need for information that hospital pharmacists are looking for. Conducting stability studies by hospital pharmacy teams should be encouraged.